Bridging the institutional gap for Juvenile court-annexed mediation in Kenya - Amiani, F. S. (Strathmore University, 2024)
Court-annexed mediation (CAM) is a method of resolving disputes restoratively and it has the potential to propel the juvenile justice system to be in line with the ‘best interests of the child’ principle. Its effects, however, are yet to be realized since the institutions to conduct this process seem to be nonexistent. This study discusses the institutional gap in Kenya and a case study of Kenya and Australia is conducted. The contrast in the institutional framework between the two countries is highlighted. The study used a deductive approach to how restorative access to justice is practised in various legal systems and how such practices can be modified to fit the Kenyan context. This is also complemented by an institutional analysis to show how juvenile mediation programmes work in other legal systems in terms of structural procedure. Reference was made to primary sources in the form of books, articles, and reports, which discuss juvenile court-annexed mediation, as well as access to justice. The study further discusses child-inclusive mediation and how this could play an important role in ensuring both the juvenile and the victim benefit from the mediation process in the juvenile justice sector. It is recommended that child participation in the justice system be supported by way of sensitising communities to uphold ADR practices and allocating resources equitably in the justice sector.
Full - text undergraduate research project